Evaluation of nonconformities related to sanitary regulations applied to clinical laboratories in public hospital in the city of Rio de Janeiro-RJ from November 2016 to November 2017 - Costa,Samuel F. (2018)
ABSTRACT The study presents the main nonconformities related to the sanitary regulations found in clinical laboratory analysis (CLA) attached to a public hospital in the city of Rio de Janeiro (RJ) from November 2016 to November 2017. The evaluation of the nonconformities related to sanitary conditions is fundamental to ensure the goals in improving quality control, increasing the reliability of the results generated and reducing health risks. Through the evaluation of 20 federal and municipal public health laboratories, it was possible to analyze the main sanitary nonconformities in the different laboratories phases (pre-analytical, analytical and post-analytical), evaluating, through Fisher's exact test, the frequency and trend distribution of reported nonconformities. One hundred percent (100%) of the clinical analysis laboratories presented at least, one nonconformity. Among those with the highest frequencies of nonconformity related to sanitary conditions are those related to the lack of standard operating procedures (SOPs), presenting 45.5% in clinical analysis laboratories of federal hospitals and 66.7% in clinical analysis laboratories of municipal hospitals. Moreover flaws in the cleaning, disinfection and sterilization processes, in equipments and in the presence of the technical manager (TM) throughout the working hours. Sanitary surveillance actions seek to provide health services to the population that comply with established quality standards, even though the identification of nonconformities subsidizes the adoption of corrective actions by the health establishment.